Teologi Birokrasi Yesus dan Para Rasul: Paradigma Alternatif untuk Kepemimpinan Etis di Indonesia - Siang, Harun; Sanderan, Rannu (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2025)
This research examines the model of the theology of bureaucracy of Jesus and the apostles in the New Testament as an alternative paradigm for ethical leadership in Indonesia. This paradigm emphasizes the principles of service, humility, and sacrifice, which differ from traditional bureaucracy that places more emphasis on hierarchy, authority, and power. Using qualitative methodology with biblical text analysis and a hermeneutic approach, this research also explores the contextualization of Roman bureaucracy and contemporary Indonesian bureaucracy. The research findings indicate that the application of Jesus' leadership principles can enhance integrity and service orientation in public policy. This paper contributes to the development of bureaucratic theology literature and provides practical guidance for Christian leaders, academics, and theology students in understanding the relationship between religious ethics and more inclusive and responsible public administration. These findings open up opportunities for further research in formulating public leadership models relevant to the bureaucratic challenges in Indonesia.